Social control and trust in the New Zealand Environmental Movement - O'Brien, Thomas (Sage, 2013)
Escalating concern regarding environmental issues has resulted in an increase in the number and scope of environmental movements internationally. The diversity and proactive nature of these movements has put pressure on public (state) actors to address challenges and engage with movement actors. Engagement is not universally positive and can lead to attempts at disruption or subversion of challenging movements. This article examines the impact of perceived state subversion on trust within the New Zealand environmental movement through the alleged use of spies. The analysis finds that short-term emotional reactions within the movement that led to questioning of relationships were outweighed by longer-term pragmatic view about the need to maintain collective action